ИННОВАЦИОН РИВОЖЛАНИШ ‒ ЖАМИЯТНИНГ ЯНГИ ТАРАҚҚИЁТ БОСҚИЧИДА МУҲИМ ОМИЛ (Scientific journal of the Fergana State University, 2019)
In the article the author investigates the matters of insertion of the innovations in new conditions as an important factor of a sustainable development of a society. The attempt to connect modern problems of perfection of system of insertion of innovations in society with reforming  processes in the country is made.